Efficacy of INtensive Treatment vs. Standard Treatment of COmpound DanshEn Dripping Pills in Refractory Angina Patients With Incomplete Revascularization (INCODER Study): Study Protocol for a Multicenter, Double-Blind, Randomized Controlled, Superiority Trial - Wu, Zexuan; Xu, Danping; Wu, Zhen; Chen, Ailan; Liu, Lijuan; Ling, Li; Zhou, Yan; Liu, Duoduo; Liu, Yin; Dong, Yugang; Chen, Yili (Frontiers in Cardiovascular Medicine, 2022)
Introduction Patients with incomplete revascularization (ICR) tend to develop refractory angina despite optimal medical therapy. The Compound Danshen Dripping Pills (CDDP) is a widely used antianginal drug in China and is shown to significantly alleviate myocardial ischemia. Previous studies showed dose-efficacy tendency when increasing doses of CDDP. This study aims to investigate the efficacy and safety of intensive doses of CDDP in patients with refractory angina with ICR. Methods and Analysis The INCODER study is a multicenter, double-blind, randomized controlled, superiority trial. We plan to recruit 250 patients aged 18–85 years with a diagnosis of refractory angina with ICR. Patients will be randomized (1:1) to intensive treatment group (CDDP 20 pills three times per day) or standard treatment group (10 pills CDDP and 10 pills placebo three times per day). Patients will have a 6-week medication period and be followed up every 2 weeks. The primary endpoint is the change of total exercise time from baseline to week 6 as assessed by cardiopulmonary exercise testing (CPET). Secondary endpoints include changes in the frequency of angina, Canadian Cardiovascular Society angina class, nitroglycerin use, Seattle Angina Questionnaire scores, peak oxygen uptake (VO2 peak) and other parameters as measured by CPET, and the levels of plasma C-reactive protein, homocysteine, and N-terminal pro-B-type natriuretic peptide. Safety events related to CDDP use will be monitored. Ethics and Dissemination The research had been approved by the Clinical research and laboratory animal ethics committee of the First Affiliated Hospital, Sun Yat-sen University ([2019]65). The results will be reported through peer-reviewed journals, seminars, and conference presentations. Trial Registration Number www.chictr.org.cn (ChiCTR2000032384). Registered on 27 April 2020.